Crystallization, microstructure and mechanical behavior of titanium doped barium fluormica glass‐ceramics. Issue 4 (10th January 2019) - Mallik, Amit; Saha, Sumit
Abstract: Crystallization, microstructure and mechanical behavior of TiO2 doped barium fluorphlogopite glass‐ceramics were systematically studied. TiO2 was used as a doper nucleant in the BaO·4MgO·Al2 O3 ·6SiO2 ·2MgF2 glass system. Melting technique was adopted to prepare the glass samples which were analyzed by differential thermal analysis (DTA), X‐ray diffraction, scanning electron microscopy, and micro hardness indenter. The DTA study demonstrated that the crystallization exotherm of fluorphlogopite mica appeared in the temperature window of 886‐903°C. In this investigation, four glass samples were prepared using 2 (MA1), 4 (MA2), 6 (MA3), and 8 (MA4) wt% of TiO2. Glass transition ( T g ) and peak crystallization ( T p ) temperatures escalated with an increase in the TiO2 content from 2 (MA1) to 4 wt% (MA2). However, beyond this value, T g and T p decreased with a surge in TiO2 content from 6 (MA3) to 8 wt% (MA4). Nevertheless, with a gradual rise in the TiO2 content, the crystals of the glass‐ceramics became enlarged and subsequently exhibited mechanical properties, such as hardness, fracture toughness, and machinability. Therefore, in solid oxide fuel cell applications, TiO2 is a promising nucleating agent to generate fluorphlogopite mica‐based glass‐ceramics.